2009
DOI: 10.1017/s1368980009005230
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss by mobile phone: a 1-year effectiveness study

Abstract: This mobile phone weight-loss programme was effective in short- and long-term weight loss. As a minimum-advice, maximal-contact programme, it offers ideas for future weight-loss programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
392
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(406 citation statements)
references
References 27 publications
12
392
1
1
Order By: Relevance
“…A study from Sweden evaluated the effectiveness of a weight loss program delivered via SMS. The program addressed regulation of diet as well physical activity and reported that by 12 months the experimental group had lost significantly more weight than the control group (12). A systematic review published in 2016 reviewed 15 studies evaluating mHealth and eHealth interventions for promotion of healthy diets and physical activity in LAMI countries.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Sweden evaluated the effectiveness of a weight loss program delivered via SMS. The program addressed regulation of diet as well physical activity and reported that by 12 months the experimental group had lost significantly more weight than the control group (12). A systematic review published in 2016 reviewed 15 studies evaluating mHealth and eHealth interventions for promotion of healthy diets and physical activity in LAMI countries.…”
Section: Discussionmentioning
confidence: 99%
“…19,20,36,[58][59][60]62,[64][65][66][67][68][69][70]72,74 Intervention participants were more likely to lose ≥ 10% of their baseline body weight compared with controls. There was no evidence that the effect of treatment differed based on focus of intervention (Table 3).…”
Section: Weight Outcomesmentioning
confidence: 99%
“…Andrews et al 22 (1) Andrews et al 22 (2) Appel et al 19 Balducci et al 25 Bennett et al 27 Burke et al 34 (F) Burke et al 34 (M) Christian et al 33 Cohen et al 35 de Mello et al 50 Dekkers et al 17 DPP 84 (1) Foster-Schubert et al 49 (1F) Foster-Schubert et al 49 (2F) Foster-Schubert et al 49 (3F) Haapala et al 36 Janus et al 53 Kirby et al 23 Kulzer et al 37 Langford et al 38 Lim et al 31 Ma et al 47 Martin et al 39 (F) Morey et al 46 Nakade et al 52 (F) Nakade et al 52 (M) Nanchahal et al 54 Parikh et al 45 Patrick et al 18 (M) Ross et al 28 (F) Ross et al 28 (M) Stevens et al 40 (F) Stevens et al 40 (M) Stevens et al 41 (F) Stevens et al 41 (M) ter Bogt et al 21 Vissers et al 26 (1) Vissers et al 26 (2) Wadden et al 20 Wood et al 42 (1M) Wood et al 42 (2M) Wood et al 43 (1F) Wood et al 43 (1M) Wood et al 43 (2F) Wood et al …”
Section: Weight Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the characteristics of these types of mobile technologies, such as asynchrony (36)(37)(38)(39), the ease with which privacy can be maintained (40), as well as the light workload for the participants (one minute per day), helped to increase participation. In addition, the recording of foods/drinks intake was to be completed during 28 consecutive days using the application and at the end of this period using the short paper FFQ, minimizing the likelihood of changes in dietary intake.…”
Section: Strengths and Limitationsmentioning
confidence: 99%